The bending analysis of thin composite plate under steady temperature field - Nguyen, Dinh Duc (H. : ĐHQGHN, 2017)
Composite material with polymer matrix - titanium particle is widely applied in Vietnam, today. In this paper, the bending of thin polymer composite plate with Titaniump articles under the effect of the steady temperature field is investigated. The paper has established the boundary problem of a simply supported composite plate reinforced by particles under the influence of steady heat transfer process. Using the Navier’s method to solve the problem, an analytic solution of the bending plate given in tiie form of double trigonometric series is obtained. Base on the analytic result, a numerical test is done to find suitable material and clarily the influence of the particles.